2015
DOI: 10.1038/nbt.3269
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of intronic and exonic reads in RNA-seq data characterizes transcriptional and post-transcriptional regulation

Abstract: A n A ly s i s RNA-seq experiments generate reads derived not only from mature RNA transcripts but also from pre-mRNA. Here we present a computational approach called exon-intron split analysis (EISA) that measures changes in mature RNA and pre-mRNA reads across different experimental conditions to quantify transcriptional and post-transcriptional regulation of gene expression. We apply EISA to 17 diverse data sets to show that most intronic reads arise from nuclear RNA and changes in intronic read counts accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
368
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(403 citation statements)
references
References 53 publications
15
368
0
1
Order By: Relevance
“…Although we initially envisioned using exogenous spike-ins for a normalization approach, we were surprised that this framework was surpassed by intron normalization. Despite using oligo(dT) selection to generate our libraries, we found that introns were abundant in our datasets; these reads are possibly derived from processing intermediates and are consistent with previous observations (Gaidatzis et al 2015). We found that intron-based normalization was effective for all datasets we examined, irrespective of the organism examined, even for datasets that were otherwise recalcitrant.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although we initially envisioned using exogenous spike-ins for a normalization approach, we were surprised that this framework was surpassed by intron normalization. Despite using oligo(dT) selection to generate our libraries, we found that introns were abundant in our datasets; these reads are possibly derived from processing intermediates and are consistent with previous observations (Gaidatzis et al 2015). We found that intron-based normalization was effective for all datasets we examined, irrespective of the organism examined, even for datasets that were otherwise recalcitrant.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with previous observations (Gaidatzis et al 2015), we noted that introns were abundant in our libraries, especially at the earliest time points, where they made up 19% of the total reads ( Figure 3A). As with the Drosophila spike-ins, the overall proportion of reads mapping to introns exhibited a time-dependent decrease ( Figure 3A), and the relative abundance of individual introns did not show a large time-dependent decrease in similarity ( Figure S2C; r s = 0.90 to 0.95), indicating that equilibrium levels were generally reached before the first time point.…”
Section: The Conceptual Underpinnings Of Metabolic Labeling and Approsupporting
confidence: 79%
“…1A). For RNA-Seq, intronic reads provide a good proxy for transcription rate and exonic reads for mRNA abundance (17). Owing to the large number of samples, we developed a simplified and faster protocol for ribosome profiling library generation, similar to that in ref.…”
Section: Resultsmentioning
confidence: 99%
“…6G). We took advantage of the RNA-Seq technology to decipher the role of transcriptional and posttranscriptional regulations (17) in the establishment of the diurnally rhythmic transcriptome in mouse liver. We concluded that transcription is the main regulator of rhythmic mRNA accumulation (66% of rhythmic mRNA are rhythmically transcribed) (Fig.…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%
“…The Integrative Genomics Viewer (www.broadinstitute.org/igv) was used to visualize genomic coverage, transcripts were assembled using Cufflinks 31 and annotated via the Genomatix software suite (Genomatix). It should be noted here that there now exist dedicated in silico pipelines 32,33 for assessing changes in gene expression based on intronic RNA levels (instead of exonic levels that standard algorithms use), and we anticipate that their implementation will further enhance the sensitivity of factory RNA-seq.…”
Section: Anticipated Resultsmentioning
confidence: 99%